PENGARUH MANAJEMEN LABA, LIKUIDITAS, LEVERAGE, DAN PROFITABILITAS TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN - Ummah, Dian Nur Hanifatul; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to examine the influence of profit management, liquidity, leverage and profitability to the disclosure level of annual financial statement on manufacturing companies which are listed in Indonesia Stock Exchange in 2012-2015 periods. The population is all manufacturing companies which are listed in Indonesia Stock Exchange in 2012-2015 periods. The sample collection has been conducted by using purposive sampling. Based on the criteria, 40 companies have been selected as the research samples. The data analysis technique has been carried out by using descriptive analysis and multiple linear regressions analysis. Based on the result of the analysis, it can be concluded that: 1) profit management does not have any influence to the disclosure level of annual financial statement. It is shown by the profit management value is more than 0.05 i.e. 0.704; 2) liquidity does not have any influence to the level of annual financial statement disclosure. It is shown by the liquidity value is more than 0.05 i.e. 0.144. 3) Leverage variable does not have any influence to the level of annual financial statement disclosure. It is shown by the leverage value is more than 0.05 i.e. 0.946; 4) profitability variable has influence to the level of annual financial statement disclosure. It is shown by the profitability value is less than 0.05 i.e. 0.002.Keywords: disclosure level, profit management, liquidity, leverage, profitability.